The Danish model and the globalizing learning economy: Lessons for developing countries - Bengt-Åke Lundvall (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2009)
Although Denmark shares with the other four Nordic countries certain attributes, such as pragmatic protestant religion, small and homogenous population, strong social democratic parties and ambitious welfare states, it also has its own characteristics. High degree of specialization in the so-called low-tech sectors, combined with high mobility and income security in labour markets (flexicurity), contributes to making the Danish system unique in the world. Denmark has experienced some stagnation in its growth over the last decade but still ranks among the top ten in the world in terms of GNP per capita, registered unemployment is less than 2 per cent (as of June 2008) while the inflation rate has remained moderate. These goals for economic policy have been realized in an environment with a high degree of income equality. In this paper we use the concepts innovation system, the learning economy and learning modes to analyse the evolution of the Danish model and what can be learnt from it.
Keywords: O10; O16; 330; economic development; welfare state; social cohesion; innovation; Wirtschaftswachstum; Sozialstaat; Innovation; Dänemark; Entwicklungsländer